ATTITUDES AND PERCEPTIONS OF MALAYSIAN ESL UNDERGRADUATES TOWARDS THE USAGE OF VLOGGING IN ENHANCING THEIR SPEAKING SKILLS - Nazirah Mahmud; Nurhazwani Yusoff; Najihah Mahmud (LET: Linguistics, Literature and English Teaching Journal)
The aim of this research is to find out the attitudes and the perceptions of the undergraduate students in a private higher institution in Malaysia, towards making video recording specifically video blogging (vlogging) to enhance their speaking skill in the target language – English. This research is also carried out to determine the advantage(s) and disadvantage(s) of using vlog for similar purpose. A quantitative design was employed in this study where a questionnaire was used to elicit data. The questionnaire touched on students’ attitudes and perceptions towards the use of vlogging in enhancing their speaking skills. The overall findings showed that the university students agreed that using vlogging can improve their English-speaking skills to a certain extent.